On memories and affections: dialogues with former students professors of FEUSP - Braga, Elizabeth dos Santos; Menezes, Roni Cleber Dias de (Faculdade de Educação/Universidade Estadual de Campinas, 2021)
This article results from the analysis of statements produced in October 2019 when commemorating the 50th anniversary of the creation of the Faculty of Education of the University of São Paulo (Feusp) and the 60th anniversary of the School of Application of the Faculty of Education of the University of São Paulo (EA-Feusp) with six former students of Feusp, who, having joined the course at different times, became, years after completing their graduation in Pedagogy, professors at the institution. With the material, we tried to thematize the elaboration of memories by the subjects about the institution itself, their formative itineraries and their connection with broader events in the political, social, cultural and educational spheres.